Taking the Perspective that a Depressive State Reflects Inflammation: Implications for the Use of Antidepressants - Littrell, Jill L. (Frontiers in Psychology, 2012)
This paper reviews both the evidence that supports the characterization of depression as an inflammatory disorder, and the different biochemical mechanisms that have been postulated for the connection between inflammation and depression. This association offers credible explanation for the short term efficacy of antidepressants, which have short term anti-inflammatory effects. Evidence for those anti-inflammatory effects is discussed. Evidence of the contrary long term effects of antidepressants, which increase rather than decrease inflammation, is also reviewed. It is argued that this increase in inflammation would predict an increase in chronicity among depressed patients that have been treated with antidepressants drugs, which has been noted in the literature. A brief discussion of alternatives for decreasing inflammation, some of which have demonstrated efficacy in ameliorating depression, is presented